2012
DOI: 10.1103/physrevb.86.220511
|View full text |Cite
|
Sign up to set email alerts
|

Hydrostatic-pressure tuning of magnetic, nonmagnetic, and superconducting states in annealed Ca(Fe1xCox)

Abstract: We report on measurements of the magnetic susceptibility and electrical resistance under He-gas pressure on single crystals of Ca(Fe1−xCox)2As2. We find that for properly heat-treated crystals with modest Co-concentration, x = 0.028, the salient ground states associated with iron-arsenide superconductors, i.e., orthorhombic/antiferromagnetic (o/afm), superconducting, and nonmagnetic collapsed-tetragonal (cT) states can be accessed all in one sample with reasonably small and truly hydrostatic pressure. This is … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
60
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(64 citation statements)
references
References 40 publications
4
60
0
Order By: Relevance
“…18 The electronic properties of the cT phase are vastly different than of the un-collapsed tetragonal (TET) phase due to the abrupt change of the electronic bandstructure, associated with the structural change 19 , e.g., the transition into the cT phase often leads to the loss of magnetism or SC. 8,9,[20][21][22][23] Therefore, studying the pressure-temperature phase diagrams and the different ground states is fundamental for understanding SC this family of materials. Some compounds with ThCr 2 Si 2 structure can support conventional superconductivity while still exhibiting intriguing ground states.…”
mentioning
confidence: 99%
“…18 The electronic properties of the cT phase are vastly different than of the un-collapsed tetragonal (TET) phase due to the abrupt change of the electronic bandstructure, associated with the structural change 19 , e.g., the transition into the cT phase often leads to the loss of magnetism or SC. 8,9,[20][21][22][23] Therefore, studying the pressure-temperature phase diagrams and the different ground states is fundamental for understanding SC this family of materials. Some compounds with ThCr 2 Si 2 structure can support conventional superconductivity while still exhibiting intriguing ground states.…”
mentioning
confidence: 99%
“…This dT c /dP value is close to that directly measured under hydrostatic pressure. 20 The dT c /dp c ≈ −20 K/kbar value is phenomenally large and provides further evidence of the extreme pressure and stress sensitivity of these compounds.…”
Section: Discussion and Summarymentioning
confidence: 99%
“…18,19 The effects of annealing and quenching were shown to be similar to those of the pressure. [18][19][20] It was suggested that the annealing and quenching process, via the precipitates, controls the amount of strain built up in the samples and this way acts similarly to a moderate applied external pressure. It was shown 19 that by careful choice of Co concentration and annealing and quenching parameters, the Ca(Fe 1−x Co x ) 2 As 2 system can by systematically and reproducibly tuned to have one of four different ground states: orthorhombic and antiferromagnetic, tetragonal and superconducting, tetragonal and nonsuperconducting, and collapsed tetragonal without magnetic order or superconductivity.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…13 In order to understand this compound, we had to commit to detailed analyses of process-property relations 14,15 as well as even pay attention to what type of grease we used to mount crystals for measurement. We found that CaFe 2 As 2 is a wonderful system, it is an inorganic superconductor with organic-like sensitivities, 16 it serves as a key example of FeAs-based superconductivity, but we had to be willing to pay the price and understand the trail we were jogging on.…”
mentioning
confidence: 99%